Intervensi Art Therapy untuk Mengurangi Perasaan Kesepian pada Warga Lansia di Balai Pelayanan Sosial Tresna Wredha Yogyakarta - Antonio, Cristopher Caesar; Sukmawati, Anastasia Suci; Rohman, Fathoni; Riyadi, Sujono (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Elderly individuals residing in nursing homes are at a higher risk of experiencing psychological problems, particularly loneliness. One nursing intervention that has been shown to address loneliness is art therapy. Purpose: This case report aims to describe the implementation of art therapy as a nursing intervention to reduce loneliness among elderly residents in a nursing home. Method: a case report design, encompassing assessment, data analysis, nursing diagnosis, planning, intervention, implementation, and evaluation. The intervention was conducted over three consecutive days, with each session lasting 10–15 minutes. The art therapy techniques utilized included drawing and traditional singing. The participants in this study were two elderly individuals residing in a nursing home who reported feelings of loneliness. Data collection methods included observation, questionnaires, interviews, literature review, and documentation of intervention outcomes. The instruments employed were the UCLA Loneliness Scale Version 3 and the Standard Operating Procedure (SOP) for art therapy. Result: Findings from the UCLA Loneliness Scale indicated a reduction in loneliness scores. The first participant’s score decreased from 55 (moderate loneliness) to 33 (no loneliness), while the second participant’s score decreased from 50 (moderate loneliness) to 30 (no loneliness). Conclusion: Art therapy demonstrated effectiveness in reducing loneliness among elderly individuals in a nursing home setting. This finding highlights the potential of art-based nursing interventions as a complementary approach to improving the psychological well-being of older adults.